Frequency and molecular basis of CD36 deficiency in Xinjiang, China - QIU Jin; LI Fei; LI Qiang; WANG Rubin; Si Kan De'er·Ai Bai Du'la; LIU Jing; CHEN Wei (Zhongguo shuxue zazhi)
[Objective] To investigate the distribution characteristics of CD36 antigen in healthy individuals in Xinjiang, China and analyze the molecular mechanisms underlying CD36 deficiency. [Methods] Flow cytometry was used to assess CD36 antigen expression on platelets from 881 healthy individuals who underwent physical examinations between June and August 2023. Differences in CD36 antigen distribution among ethnic groups were compared, and genotyping and third-generation sequencing were conducted on samples with CD36 deficiency. [Results] Among the 881 samples, 4 cases (0.5%) of CD36 type Ⅱ deficiency were identified. The deficiency frequency was 0.7% (3/430) in Han individuals and 0.3% (1/363) in Uygur individuals, with no statistically significant difference between the two groups (P>0.05). No mutations were detected in the coding regions of the deficient samples. Two samples exhibited a (TG)11 in intron 3. Among the 12 linked mutation sites, g. 55589 G>A was mutated to g. 55589G Del, while g. 55593 A del did not occur; however, g. 55591A>T was observed nearby. Additionally, 52742insGAAAA was present in 100% of the (TG)11 haplotypes, potentially representing a novel linked mutation. [Conclusion] This study indicates that the positive frequency of CD36 antigen in Xinjiang is relatively high, suggesting a low risk of alloimmune diseases in clinical practice. The (TG)11 in intron 3 is not universally present in all CD36 type Ⅱ deficiency cases, and the number of linked mutation sites extends beyond the previously reported 12.